Physiological anthropometric and motor values in relation to 500 metres running - Bekolli, L.; Ramabaja, Q.; Rashiti, N.; Shkodra, M.; Heta, G. (Journal of Education, Health and Sport, 2023)
The primary purpose of this paper is to determine and prove the impact of loads with different intensities on the treadmill on the heart frequency, as well as to prove the relationship and impact of some anthropometric and motor parameters on the physiological one in the manifest space. In harmony with the purpose of the research, three basic hypotheses have been presented that cover the anthropological research fields. In this paper, 19-year-old students of the Faculty of Sports Sciences are included. To achieve the purpose of the paper, a sample of 80 students who were regular students during the year 2022/2023 was included. Four anthropometric variables, three motor tests (running tests) and four physiological tests (pulse at rest and during loads) are included in this paper. For the three groups of the system of variables, the basic statistical and distribution parameters for each variable, as well as the measures of asymmetry and normal distribution, were calculated. Then the correlations between the variables in the manifest space, as well as the correlations between the system of variables. In order to determine the relationship between predictor variables (anthropometric and motor characteristics) and criterion variables (results of functional skills), regression analysis was applied in the manifest space. The processing of the results shows that the obtained values do not deviate from the normal distribution, which completes their metric characteristics. The impact of morphological and motor factors on heart rate results has not been proven.